2015
DOI: 10.1189/jlb.1a0114-058rr
|View full text |Cite
|
Sign up to set email alerts
|

Human blood CD1c dendritic cells stimulate IL-12-independent IFN-γ responses and have a strikingly low inflammatory profile

Abstract: Adaptive immune responses are initiated by resident myeloid tissue DC. A major fraction of tissue DC express CD1c and is thought to be derived from blood CD1c DC, an idea supported here by the observation that they express tissue-homing molecules and rapidly differentiate into cells with a tissue DC phenotype. Responses are thought to be augmented/modulated further by inflammatory moDC. Although much accepted human myeloid DC cell biology is based on moDC studies, we find these 2 DC populations to be functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Interestingly, we observed that these gut-homing CD4 + T cells, generated in the presence of RA-MoDCs, expressed augmented levels of IFN-g in an IL-12-independent manner. Recently, human DCs have been shown to induce IL-12-independent IFN-g [42]. Furthermore, there are reports where RA acts through cell-cell interaction (costimulatory pathways) to modulate IFN-g production [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we observed that these gut-homing CD4 + T cells, generated in the presence of RA-MoDCs, expressed augmented levels of IFN-g in an IL-12-independent manner. Recently, human DCs have been shown to induce IL-12-independent IFN-g [42]. Furthermore, there are reports where RA acts through cell-cell interaction (costimulatory pathways) to modulate IFN-g production [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…DCs also produce effector-polarizing cytokines that are crucial in directing effective T cell differentiation. (48) However, emerging evidence indicates that DCs can drive effector differentiation independent of cytokines. (9, 10) Our studies and others suggest that Notch ligands expressed on the surface of DCs are important in promoting the generation of different lineages of effector T cells.…”
Section: Introductionmentioning
confidence: 99%
“…The hCMRF-56 selection of BDC is clinically feasible and compatible with outpatient and hospital scheduling; nevertheless, further improvements in its efficacy are possible. It is likely, given the low inflammatory profile of mDC (including CD1c C DC, 49 the major fraction of hCMRF-56 BDC), that improved stimulation of BDC (e.g. by CD40 ligation) might increase their migration or their T-cell priming potency.…”
Section: Discussionmentioning
confidence: 99%